2018
DOI: 10.1007/s00397-018-1113-9
|View full text |Cite
|
Sign up to set email alerts
|

The time-dependent rheology of fermenting wheat flour dough: effects of salt and sugar

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…As it can be seen in Fig 1 , the initial behavior of both dough samples differs in the absolute value of |G*|, as |G*| of non-yeasted standard wheat dough is higher compared to yeasted wheat dough. This drop in |G*| for yeasted doughs has been observed previously and was related to the entrapped gas cells [ 18 , 25 27 ]. Besides CO 2 , previous work of the authors has shown that secondary yeast metabolites like ethanol or succinic acid only have a minor impact on the rheological behavior of the dough matrix under a small amplitude oscillatory strain [ 10 ].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…As it can be seen in Fig 1 , the initial behavior of both dough samples differs in the absolute value of |G*|, as |G*| of non-yeasted standard wheat dough is higher compared to yeasted wheat dough. This drop in |G*| for yeasted doughs has been observed previously and was related to the entrapped gas cells [ 18 , 25 27 ]. Besides CO 2 , previous work of the authors has shown that secondary yeast metabolites like ethanol or succinic acid only have a minor impact on the rheological behavior of the dough matrix under a small amplitude oscillatory strain [ 10 ].…”
Section: Resultssupporting
confidence: 78%
“…In this way, extensional techniques, such as lubricated squeezing flow, capillary breakup elongational rheometry, filament stretching rheometry, sentmanat extension rheometry or hyperbolic contraction flow can principally be applied [9,11,[14][15][16][17]. Especially in order to access gluten (or zein) functionality, these techniques are state-of-the-art [7,10,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…During the fermentation step, CO 2 and many secondary metabolites are generated by yeast cells and released into the dough matrix phase due to common metabolic activity, or, in case of osmotic stress, to maintain the internal redox balance [ 7 ]. An often-underestimated effect is the impact of secondary metabolites on the rheological properties of the dough matrix, clearly determining the manufacturing properties and end product characteristics [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Thus, the aim of the current study is to characterise the rheological behaviour of the fermenting dough matrix for relevant deformation types and strain rates occurring during the breadmaking process.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 , ethanol and glycerol are the main metabolites of yeast during dough fermentation (Jayaram et al ., 2013; Rezaei et al ., 2014). The softening of dough depends on glycerin content, and the gluten network structure was affected by ethanol, so dough's extensibility and ductility reduced (Mathieu, Dries, et al ., 2018; Mathieu, Ramirez, et al ., 2018). Surprisingly, the increasing ethanol content during fermentation reduced the extensibility of the dough, making it stiffer and tougher (Jayaram et al ., 2014).…”
Section: Resultsmentioning
confidence: 99%